1995
DOI: 10.1108/07363769510146787
|View full text |Cite
|
Sign up to set email alerts
|

Segmenting by consumer time shortage

Abstract: Investigates whether consumers′ time availability is an important segmentation variable in the convenience and fast‐food markets. Very time‐poor, somewhat time‐poor, and not time‐poor consumers are compared, and three types of food are examined: fast foods, frozen dinners, and ready‐to‐eat foods. For weekday dinners, similarities and differences between the three segments are investigated with respect to usage of each type of food, importance of benefits sought in a weekday dinner, and perceptions of each type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0
11

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(64 citation statements)
references
References 15 publications
1
52
0
11
Order By: Relevance
“…In this regard prior research provides helpful insights. While demographic factors have not proven successful in determining customers' individual level of convenience consciousness, individuals suffering from scarcity of time (Darian and Cohen 1995;Berry 1979), role overload, and stress (Madill-Marshall et al 1995;Reilly 1982) are highly convenience-conscious. Retailers can use these factors to determine whether their customers are convenience conscious, for example with the help of customer surveys, and accordingly decide to use round or just-below prices.…”
Section: Managerial Implicationsmentioning
confidence: 97%
See 1 more Smart Citation
“…In this regard prior research provides helpful insights. While demographic factors have not proven successful in determining customers' individual level of convenience consciousness, individuals suffering from scarcity of time (Darian and Cohen 1995;Berry 1979), role overload, and stress (Madill-Marshall et al 1995;Reilly 1982) are highly convenience-conscious. Retailers can use these factors to determine whether their customers are convenience conscious, for example with the help of customer surveys, and accordingly decide to use round or just-below prices.…”
Section: Managerial Implicationsmentioning
confidence: 97%
“…Highly convenience-conscious consumers hence put much weight on convenience aspects when shopping (Anderson 1971) and are even willing to pay a higher price for increased convenience (Swoboda 2001;Williams et al 1978). Research has identified several drivers of convenience consciousness, such as time scarcity (Darian and Cohen 1995;Berry 1979), role overload and stress (Madill-Marshall et al 1995;Reilly 1982), and the wish for higher quality of life and more leisure time (Swoboda 2001).…”
Section: Conceptualizing Convenience and Convenience Consciousnessmentioning
confidence: 98%
“…These variables are central to the second theoretical framework, namely the convenience orientation approach by Yale and Venkatesh (1986); this framework extended the resource constraints perspective by several factors determining consumers' choice of convenience products, including the appropriateness of a product and the social and cultural aspects. Although it is widely agreed that convenience is a complex and multidimensional construct (Berry, Seiders, & Grewal, 2002;Darian & Cohen, 1995;Gehrt & Yale, 1993;Gofton, 1995;Jaeger & Cardello, 2007), Jaeger and Cardello (2007) indicated that a consensus on the different elements of that construct has not yet emerged. However, there is broad agreement that effort and time contribute to the concept of convenience.…”
Section: School-based Interventionsmentioning
confidence: 97%
“…Convenience is here defined as aspects of the product which save time or energy throughout the private household's meal production chain, i.e., during shopping, storage, preparation, eating, and disposal. In a wider sense, convenience relates to home-meal replacement alternatives like eating out (Darian & Cohen, 1995). Increased demand for convenience has often been related to family demographics like both adult household members' participation in the work force (e.g., Darian & Klein, 1989;Soberon-Ferrer & Dardis, 1991), but newer research indicates that demand for convenience is best explained by households' subjective perceptions of their resource constraints (Scholderer & Grunert, 2005).…”
Section: Trends In Consumer Food Choicementioning
confidence: 99%